Nonconsumptive effects of hunting on a nontarget game bird - Jessica L. Mohlman; Rachel R. Gardner; I. B. Parnell; Nathan G. Wilhite; James A. Martin (Ecology and Evolution, 2019)
Abstract Human hunting activity and disturbance can significantly impact prey species through both consumptive and nonconsumptive effects. The nonconsumptive effects of rabbit hunting on Northern Bobwhite (Colinus virginianus; hereafter, bobwhite) are currently unknown. Increased perceived risk of predation by bobwhite during rabbit hunting events may elicit antipredator responses among bobwhite that impact fitness via changes in behavior that ultimately impact population growth. We estimated the nonconsumptive effects of rabbit hunting on bobwhite behavior using telemetry across varying rabbit hunting intensities. Movements were analyzed using Bayesian hierarchical modeling with a before‐after‐control‐impact (BACI) design to determine the effect of rabbit hunting on bobwhite. We observed an overall reduction in bobwhite movement in the presence of rabbit hunting, with a 38% (Posterior Overlap = 0.01) increase in bobwhite step length in the absence of rabbit hunting. We also observed bobwhite maintaining closer proximity to hardwood and escape cover under high rabbit hunting intensity, with a 59% (Posterior Overlap = 0.03) increase in distance from hardwood and a 28% (Posterior Overlap = 0.14) increase in distance from escape cover when rabbit hunting was removed. Synthesis and applications. Heightened antipredator behavior through decreased movement may assist with bobwhite predator avoidance. However, decreased movement and increased use of poor habitats may also have negative effects as a result of reduced foraging time or increased susceptibility to other predators. Future research should attempt to quantify the effect of decreased movement on bobwhite fitness through the evaluation of foraging time and survival in order to continue to improve management efforts for the species.